Prasa polska wobec zaangażowana Niemiec i Francji w kryzys polityczny na Ukrainie (luty–maj 2014) - Barabasz, Adam (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2015)
W artykule zaprezentowano opinie publicystów prasy polskiej na temat zaangażowania Niemiec i Francji w konflikt rosyjsko-ukraiński w 2014 roku. W artykule oceniono także postawę Unii Europejskiej (w tym Niemiec i Francji) wobec działań Kremla sprowadzających się do aneksji Krymu i destabilizacji regionu. Oceniono również ewentualne skutki wprowadzenia przez społeczność międzynarodową sankcji ekonomicznych i politycznych wobec Rosji.

he paper presents the opinions of Polish journalists concerning the involvement of Germany and France in the Russian-Ukrainian conflict in 2014. The paper also assesses the attitude of the European Union (including Germany and France) towards the Kremlin’s annexation of Crimea and the destabilisation of this region. The potential outcomes of the economic and political sanctions imposed by the international community on Russia are also evaluated.
The attitude of the Polish print media towards German and French involvement in the political crisis in Ukraine (February–May 2014)
Keywords: kryzys polityczny; imperializm; sankcje; “anschulls”; destabilizacja; Unia Europejska; political crisis; imperialism; sanctions; anschluss; destabilisation; European Union